Students' Difficulties in Comprehending Hortatory Text at SMAN 1 Luhak Nan Duo Pasaman Barat - Niken Safitri; Yetti Zainil (Journal of English Language Teaching, 2020)
The students of SMAN 1 Luhak Nan Duo find it difficult in comprehending hortatory exposition text. It can be seen from the daily test result of the student, and the interview with the English teacher. Therefore, this research was aimed to find out the students’ difficulties in comprehending hortatory exposition text at SMA N 1 Luhak Nan Duo. The subject of this research was the third year students of SMA N 1 Luhak Nan Duo. Out of 270 students, 20% of them were chosen to be the sample by using cluster random sampling technique. The data were collected by using a reading test and interview guideline. The results of this research show that from 162 total frequent for each indicator. The first highest percentage of the wrong answers made by the students was in identifying language feature question. There were 96 total incorrect answers with the percentage 59.26% of identifying language features. The second highest percentage of wrong answers made by the students was in identifying thesis statement questions. There were 76 total incorrect answers with the percentage 46.91% of identifying thesis statement. Then, the third highest is in identifying argumentation question, the fourth highest is in identifying recommendation question, and the last highest one is in identifying thesis statement question. Related to the cause of difficulties, it was the language factor that is students difficult for the students to understand the long sentence in the text, it is difficult for the students to understand vocabulary in text, and the last factor was the lack of reading strategies. It can be concluded that SMAN 1 Luhak Nan Duo students find it difficult to comprehending hortatory exposition text. It proves that more than 50% of the students cannot answer hortatory exposition text correctly. It is caused by the student difficulties in understanding the long sentence in the text, difficult to understand the vocabulary in the text, and the lack of reading strategies itself.